2019
DOI: 10.1123/japa.2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Change Techniques Used in Theory of Planned Behavior Physical Activity Interventions Among Older Adults: A Systematic Review

Abstract: Physical activity interventions among older adults vary widely in the techniques used to elicit behavior change. The purpose of this systematic review was to determine what behavior change techniques (BCTs) are used in interventions to increase physical activity among older adults using the theory of planned behavior and to make suggestions for BCTs that appear to be more effective. A database search identified peer-reviewed articles documenting interventions based on the theory of planned behavior. Seven arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Action planning was considered as an essential component in diabetes self-management programmes [26,27]. A recent systematic review reported that action planning was one of the most commonly used techniques in physical activity interventions amongst older adults [28]. Unlike the study undertaken by O'Donnell et al in 2018 [29], which asked the participants to self-report whether they conducted the actions at 1…”
Section: Discussionmentioning
confidence: 99%
“…Action planning was considered as an essential component in diabetes self-management programmes [26,27]. A recent systematic review reported that action planning was one of the most commonly used techniques in physical activity interventions amongst older adults [28]. Unlike the study undertaken by O'Donnell et al in 2018 [29], which asked the participants to self-report whether they conducted the actions at 1…”
Section: Discussionmentioning
confidence: 99%
“…Action planning was considered as an essential component in diabetes self-management programmes [26,27]. A recent systematic review reported that action planning was one of the most commonly used techniques in physical activity interventions amongst older adults [28]. Unlike the study undertaken by O’Donnell et al in 2018 [29], which asked the participants to self-report whether they conducted the actions at 1 week and 3 months after planning the action (doing exercise), the current study conducted subjective measurements (using accelerometers and senior fitness tests) to assess the actions taken at Week 10 (which was four weeks after planning the action).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The TPB and SOC have been used in the exercise domain, but the TPB may be a more comprehensive and sophisticated model for explaining why people change their health behaviors. 15 Many studies have used TPB as a framework for understanding the stages of change in the western context, 17 but no studies to our knowledge have explored the utility of TPB and additional constructs in predicting exercise in patients with type 2 diabetes. Therefore, we hypothesized that the stage of exercise would be influenced by constructs of extend TPB and intention would be a significant mediator (as shown in Figure 1).…”
Section: Socmentioning
confidence: 99%